2016
DOI: 10.1038/pcan.2016.54
|View full text |Cite
|
Sign up to set email alerts
|

The role of salvage extended lymph node dissection in patients with rising PSA and PET/CT scan detected nodal recurrence of prostate cancer

Abstract: sLND can be performed without significant complications and achieves an immediate BR, thus allowing a significant postponement of systemic therapy in selected patients with BCR and nodal recurrence of PCa. Therefore, sLND following Ga-PSMA PET/CT should be considered as part of a multimodal diagnostic and treatment concept for selective patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 48 publications
0
21
1
4
Order By: Relevance
“…The present study adds to the scarce literature available on 68 Ga‐PSMA‐guided‐SLND and, to our knowledge, is the second study reporting on the feasibility and early oncological results of RASND, after the study by Montorsi et al . Recently, Porres et al reported on the largest cohort of patients who underwent open‐SLND based on F‐18 fluoroethylcholine ( 18 FEC)‐detected (38 patients) and 68 Ga‐PSMA PET/CT‐detected (49 patients) oligometastatic nodal recurrence. They reported complete treatment response in 27.5% of patients based on a post‐SLND PSA level <0.2 ng/mL, with 61/87 (70%) patients having positive histopathology.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The present study adds to the scarce literature available on 68 Ga‐PSMA‐guided‐SLND and, to our knowledge, is the second study reporting on the feasibility and early oncological results of RASND, after the study by Montorsi et al . Recently, Porres et al reported on the largest cohort of patients who underwent open‐SLND based on F‐18 fluoroethylcholine ( 18 FEC)‐detected (38 patients) and 68 Ga‐PSMA PET/CT‐detected (49 patients) oligometastatic nodal recurrence. They reported complete treatment response in 27.5% of patients based on a post‐SLND PSA level <0.2 ng/mL, with 61/87 (70%) patients having positive histopathology.…”
Section: Discussionmentioning
confidence: 70%
“…Thirdy, the median follow‐up was longer than that of the first report on RASND. Finally, we performed our analysis using both broad and strict definitions of treatment response, given that a lower post‐treatment PSA is a strong predictor of BCR‐free survival after primary treatment . We show RASND to be a safe and feasible operation in the hands of experienced robot‐assisted surgeons, with no patients in our cohort experiencing intra‐operative complications or postoperative Clavien–Dindo grade ≥3 complications, even in the setting of previous pelvic radiotherapy.…”
Section: Discussionmentioning
confidence: 92%
“…A German study of sLND investigated outcomes of surgery in patients with recurrent prostate cancer with lymphatic disease detected on imaging. 48 49 This patient population was free from additional treatment in 46.2% of cases at last follow up. As with these studies, most evidence for sLND is in patients who underwent RP for primary treatment.…”
Section: Treatment Of Oligometastatic Diseasementioning
confidence: 85%
“…Объяснить это можно и тем, что большая часть публикаций базируются на ретроспективных исследованиях, основанных на визуализирующих методах до появления ПЭТ / КТ с 68 Ga-ПСМА [22]. При этом приемлемая диагностическая ценность ПЭТ / КТ с холином достигается при уровне ПСА >2 нг / мл, а значительная часть пациентов, включаемых в исследования СЛАЭ, уже подверглись лучевой или гормональной терапии [23]. Кроме того, точность определения очагов лимфогенного поражения при рецидиве РПЖ с помощью ПЭТ / КТ с холином зависит от уровня ПСА перед исследованием, индексом Глисона и других клинических факторов [24].…”
Section: Discussionunclassified